The Role of Islamic Religious Education Teachers in Teaching Prayer Times: A Fiqh and Astronomical Perspective - Mutiara, Sri; Arrohmatan, Arrohmatan (CV. Tripe Konsultan, 2024)
This research aimed to analyze the role of Islamic Religious Education in exploring how fiqh and falak contribute to determining the precise timing of prayers. Prayer is one of the fundamental pillars of Islam and must be performed according to its prescribed times. In the Qur'an and Hadith, the times for prayer are mentioned based on the movement of sunlight as seen from the earth (Ru’yah Methode). However, due to changes in natural phenomena, sunlight is not always visible from the earth because of clouds or other factors. Therefore, it needs to be compared with the science of astronomy or astronomy, which has proven to be accurate and valid (Hisab Methode). Thus, in this case, there is a mutualistic symbiosis, where what is done by the ru’yah methode can be used as empirical evidence of the results of the hisab Methode, and vice versa. Islamic Religious Education teachers play an important role in guiding students to understand prayer times from the perspective of fiqh and astronomy.